2005
DOI: 10.1038/sj.onc.1209029
|View full text |Cite
|
Sign up to set email alerts
|

Hair follicle defects and squamous cell carcinoma formation in Smad4 conditional knockout mouse skin

Abstract: Smad4 is the common mediator for TGFb signals, which play important functions in many biological processes. To study the role of Smad4 in skin development and epidermal tumorigenesis, we disrupted this gene in skin using the Cre-loxP approach. We showed that absence of Smad4 blocked hair follicle differentiation and cycling, leading to a progressive hair loss of mutant (MT) mice. MT hair follicles exhibited diminished expression of Lef1, and increased proliferative cells in the outer root sheath. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 45 publications
4
119
2
1
Order By: Relevance
“…In mice, loss of Smad4 results in early embryonic lethality because of impaired extraembryonic membrane formation and decreased epiblast proliferation (Sirard et al, 1998;Yang et al, 1998), whereas Smad4 heterozygous mice developed gastric polyposis and cancer because of haploinsufficiency (Takaku et al, 1999;Xu et al, 2000). Using tissue-specific knockout of Smad4 (Yang et al, 2002), we, along with others, showed that Smad4 deficiency could cause tumor formation in mammary tissue (Li et al, 2003), skin (Yang et al, 2005;Qiao et al, 2006), liver , forestomach (Teng et al, 2006) and colon (Kim et al, 2006). A recent study revealed that loss of Smad4 alone does not initiate pancreatic cancer formation, although it accelerates tumor formation on activation of oncogenic signaling, such as Kras (Izeradjene et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, loss of Smad4 results in early embryonic lethality because of impaired extraembryonic membrane formation and decreased epiblast proliferation (Sirard et al, 1998;Yang et al, 1998), whereas Smad4 heterozygous mice developed gastric polyposis and cancer because of haploinsufficiency (Takaku et al, 1999;Xu et al, 2000). Using tissue-specific knockout of Smad4 (Yang et al, 2002), we, along with others, showed that Smad4 deficiency could cause tumor formation in mammary tissue (Li et al, 2003), skin (Yang et al, 2005;Qiao et al, 2006), liver , forestomach (Teng et al, 2006) and colon (Kim et al, 2006). A recent study revealed that loss of Smad4 alone does not initiate pancreatic cancer formation, although it accelerates tumor formation on activation of oncogenic signaling, such as Kras (Izeradjene et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…19 Skin-specific disruption of Smad4 results in increased epidermal proliferation consequently leading to squamous cell carcinoma formation. 20,21 Antitumor activity of BMPs may also be regulated by extracellular BMP inhibitors: expression of the BMP antagonist gremlin increased in basal cell carcinomas, in which gremlin promotes and BMPs inhibit cell proliferation. 22 However, mechanisms and downstream targets that mediate tumor suppressor function of the BMP signaling pathway in skin remain to be explored.…”
mentioning
confidence: 99%
“…The tumor suppressor, Smad4, which has been demonstrated to function constitutively in the transforming growth factor-β signaling pathway, is often mutated or deleted in various malignant neoplasms, including prostate, pancreatic and colorectal cancer (25). A previous study has demonstrated that conditional knockout of Smad4 was associated with hair follicle defects and cSCC formation in mice (26). In addition, our previous study identified the downregulation of Smad4 in a human cSCC (A431) cell line (14).…”
Section: A B C Dmentioning
confidence: 99%